Determinants of Green Purchase Behavior: An Implication of Theory of Reasoned Action - Liaquat, Malka; Iqbal, Iram; Munir, Sana; Waheed, Noorulain (Pakistan Journal of Humanities and Social Sciences, 2024)
This research aims to understand the factors that influence consumer green purchasing behavior. A theoretical model of TRA and TPB has been applied to study consumer behavior. For analyzing the model 540 middle income-earners of Multan are selected with a non-probability conviction sampling technique has been used. The data has been analyzed using the PLS-SEM technique. The results obtained show a positive association between Intention-Behavior, Attitude-Intention-Behavior, Subjective Norms-Intention-Behavior, Consumer Perceived Environmental Concern-Intention-Behavior, and Green Product Knowledge-Intention-Behavior. This study enhances the understanding of consumer behavior in the Southern belt of Pakistan by adding more insight into the literature on TRA and TPB. The unique concept of this study is the Green Product Knowledge that has been widely used in marketing research but still fewer studies have focused on the impact of GPK.